Potential failure of Soekarno Bridge Foundation Cause of Liquifaction - F. J. Manopo; A.G.D. Warouw; J.R. Talumepa; C.J. Manoppo (Lowland Technology International, 2019)
Earthquake occurring may trigger many secondary hazards. One of those hazards is liquefaction which is a phenomenon where part of soil loses it stiffness due to cyclic load. This paper evaluates the liquefaction potential of Ir. Soekarno Bridge located in Manado, Indonesia using its own soil properties acquired from standard penetration test (SPT). Using Simplified Seed & Idriss (1971) as the basis method, based on this method, if the safety factor value exceeds one, the soil has a liquefaction potential. Calculation were done using NovoLiq software with the peak ground acceleration (PGA) = 0.732 g and shallow water table. Analysis result by applying previous soil and earthquake parameters shows that there is a potential of liquefaction on the bridge’s foundation at the layer I ~ II (0 ~ 12m). Further analysis of the foundation stability against liquefaction using Pile Group GEO5 software shows there is increasing of horizontal displacement by 19.4 mm at service load, settlement increase by 0.7 mm at service load, and bearing capacity wearing off equal to 19008.45 kN. Based on analysis results, we conclude that the Ir. Soekarno Bridge have a potential of liquefaction during 7.5 Mw earthquake.